The social work with the large families in Kharkiv - Сичова, В. В.; Ібрагім, Ю. С. (SOCIOPROSTIR: the Interdisciplinary Online Collection of Scientific Works on Sociology and Social Work, 2018)
The article is written for to examine how local authorities and public organizations realize the social work with the large families in Kharkov. Concrete statistical data have already shown that systematic and quality social work with such type of families contributes to increase their number. Also, within the framework of this article are determined the problems of the conduction of full-fledged social work with the large families of Kharkov that were noted after 2014. At the end of the article are proposed and explained the main factors of improving of the social well-being with families with many children, namely interaction of local authorities and public organizations, as well as involving of large families into socially useful activities.